The regulation of public morality and eugenics: a productive alliance between the Catholic Church and Italian Fascism. Issue 3 (August 2020) - Pozzi, Lucia
Abstract : Historical research acknowledges only cursorily the Catholic contribution to eugenics. Yet there is a substantial link between Catholic discourses on morality and the emergence of Italian eugenics. In this essay I argue that sexual normalisation was a key source of consensus. Masculine and patriarchal values strengthened the strategic collaboration between Fascist demographic policies, the Italian interpretation of eugenics, and Catholic doctrine. I draw on archival and printed material to show that the control of public morality and the support for reproduction met both Catholic and Fascist interests. In particular, I focus on the alliance between the State and the Catholic Church working against 'the contraceptive mentality'. Mussolini wanted to stimulate religious sentiment as a basis for the fight against depopulation. The Catholic Church desired a set of laws against immorality, birth control and abortion. In this way, Fascism and the Catholic Church found a solid cultural agreement around restoring traditional mores, patriarchal values, and gender hierarchy.